The human factor in digital transformation: why technology is not enough - Daniela-Aida IONESCU (Revista de Management Comparat International)
Despite consistent investments in technologies, most digital transformation (DT) initiatives still fail to deliver sustainable outcomes. This paper argues that the root cause of this poor performance comes from the human dimension of transformation. DT is enabled by technologies, but shaped by leadership styles, organisational capabilities and culture. These components of the human dimension work together and are reinforced by the bottom-up experiences of employees. Resistance is seen here not as an obstacle, but as a symptom of unmet needs, conflicting demands and organisational misalignments. The paper proposes a view of transformation where people and technologies shape one another over time. To succeed, organisations need to align leadership direction with malleable capabilities and behaviours embedded in the organisational culture. Future research should investigate how the human aspects evolve across roles and layers of the organisation and how leaders can actually mobilise people to enable sustainable transformation.